Prediction of Time to Delivery Week-by-Week in Women with a Triplet Pregnancy - van de Mheen, L.; Ravelli, A. C.; Oudijk, M. A.; Bijvank, S. Nij; Porath, M. M.; Duvekot, J. J.; Scholtenhuis, M. A. G. Holswilder-Olde; Bloemenkamp, K. W. M.; Scheepers, H. C. J.; Woiski, M.; van Pampus, M. G.; Groot, C. J. de; Pajkrt, E.; Mol, B. W. J. (American Journal of Perinatology, 2016)
Objective Some clinicians advise prophylactic administration of antenatal steroids for fetal lung maturation in women with a triplet pregnancy. However, the effect of corticosteroids is limited to 10 to 14 days after administration. The aim of this study was to assess the natural course of triplet pregnancies to allow a better anticipation for administration of corticosteroids.Study Design We collected data on all triplet pregnancies in the Netherlands from 1999 to 2007 from the Netherlands Perinatal Registration. We calculated time to delivery, the risk of delivery in 2-week intervals at different gestational ages, and the time frame between hospital admission and delivery of the first child.Results Median gestational age at delivery of 494 women with a triplet pregnancy was 33+4 weeks (interquartile range of 31–35+1 weeks). Twenty-one women (4.3%) delivered between 22 and 24 weeks and 146 women (29.6%) delivered before 32 weeks. At a gestational age of 24 weeks, the chance to deliver within the next week was 0.6%. For 26, 28, 30, 31, and 32 weeks, these risks were 2.4, 2.5, 8.1, 7, and 16.7%, respectively.Conclusion Before 32 weeks of gestation, prophylactic administration of steroids is not indicated as the risk to deliver within 7 days is < 10%.
Keywords: triplet pregnancy; preterm birth; antenatal steroid treatment; neonatal outcome